2018
DOI: 10.1002/brb3.944
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the impact of chronic high‐altitude exposure on visual spatial attention using the ERP approach

Abstract: IntroductionPrevious studies have reported the slowing of reaction times to attentionally demanding tasks due to a reduction in cognitive resource as a result of chronic high‐altitude exposure. However, it is still largely unknown whether this reaction slowness can be attributed to the attentional allocation change and/or response patterns.MethodsTo clarify this issue, this study investigated attention‐related (N2pc and N2 cc) and response‐related (MP and RAP) event‐related potentials (ERPs) to identify the pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 38 publications
(57 reference statements)
2
17
0
Order By: Relevance
“…Interestingly, delayed RTs of HA residents were seen not only for deviant stimuli but also for frequent, standard stimuli, indicating that individuals living in HA areas may have disrupted behavioral RTs in general. These results are consistent with previous studies demonstrating longer RTs on measures of attention, mental rotation, and memory for HA immigrants compared with sealevel residents (Bokura et al, 2001;Zhang et al, 2013Zhang et al, , 2018aWang et al, 2015). From the behavioral view, it seems that longterm exposure (at least 3 years) to HAs influences cognitive abilities and RTs.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Interestingly, delayed RTs of HA residents were seen not only for deviant stimuli but also for frequent, standard stimuli, indicating that individuals living in HA areas may have disrupted behavioral RTs in general. These results are consistent with previous studies demonstrating longer RTs on measures of attention, mental rotation, and memory for HA immigrants compared with sealevel residents (Bokura et al, 2001;Zhang et al, 2013Zhang et al, , 2018aWang et al, 2015). From the behavioral view, it seems that longterm exposure (at least 3 years) to HAs influences cognitive abilities and RTs.…”
Section: Discussionsupporting
confidence: 91%
“…At the neuroimaging level, N2 and P3 amplitudes were maximal at frontocentral sites, consistent with these ERP components marking conflict monitoring and response inhibition indices of BIC in oddball paradigms (Liang et al, 2018;Ren et al, 2019). However, these components were significantly attenuated for participants in the HA group relative to individuals in the LA group (Bokura et al, 2001;Zhang et al, 2013Zhang et al, , 2018aWang et al, 2015). Moreover, Group × Stimulus Type interactions did not reach significance.…”
Section: Discussionsupporting
confidence: 56%
“…In terms of research methods, early studies mainly recorded responses to various psychological tasks, or adopted traditional psychophysical methods and neuropsychological tests [ 12 ]. With the development of cognitive neuroscience research techniques such as event related potentials (ERP) and functional magnetic resonance imaging (fMRI), researchers have begun to explore the brain mechanisms underlying the effects of long-term high-altitude hypoxia exposure on cognitive function [ 13 , 14 , 15 , 16 , 17 , 18 ]. Previous studies on long-term plateau environmental hypoxia mainly focused on the following two groups of people [ 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…A systematic literature review showed that visual cognitions are most easily impaired after people who live at sea level ascend to plateaus for anywhere from a day to dozens of days (Petrassi et al, 2012 ). For example, previous studies have shown that hypobaric hypoxia caused impairments in visuospatial memory (Cavaletti & Tredici, 1993 ; Hornbein et al, 1989 ; Kramer et al, 1993 ), visuospatial transformation (Denison et al, 1966 ), visual monitoring (Beer et al, 2017 ), visual orientation (Zhang, Ma, et al, 2018 ), visual search (Zhang, Zhang, et al, 2018 ), visual construction (Zhang et al, 2011 ), visuospatial executive (Sharma et al, 2014 ), visuospatial working memory (Ma et al, 2019 ; Ray et al, 2019 ; Yan et al, 2011 ), and color perception (Feigl et al, 2011 ; Karakucuk et al 2004 ). However, the mechanisms underlying the impairments of visual cognitions remain unclear.…”
Section: Introductionmentioning
confidence: 99%
“…The effects of hypobaric hypoxia on brain neuronal activities were induced by auditory (Hayashi et al, 2005 ; Kida & Imai, 1993 ; Richardson et al, 2011 ; Thakur et al, 2011 ; Wesensten et al, 1993 ), somatosensory (Nakata et al, 2017 ), and attention (Ma et al, 2018 , 2019 ; Wang et al, 2014 ; Zhang, Ma, et al, 2018 ; Zhang, Zhang, et al, 2018 ) tasks have been studied in subjects exposed to simulated altitude, rapid ascent to HA, or stayed at HA for several weeks to months. In these studies, event‐related potentials (ERPs), obtained by time‐locked averaging electroencephalography (EEG), were employed to evaluate electrophysiological processing of cognitive activity.…”
Section: Introductionmentioning
confidence: 99%